1998
DOI: 10.1016/s0022-5347(01)63574-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Significance of False-Negative Sextant Prostate Biopsies

Abstract: Our findings suggest that this 23% incidence of false-negative biopsies represents significant cancer. This relatively high incidence is important to consider in treatment modalities in which prostate biopsy may be performed to determine response to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
100
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(102 citation statements)
references
References 16 publications
1
100
0
1
Order By: Relevance
“…In our study group 332 patients (40.0 %) treated with radiation therapy were included although the diagnosis in these patients relies solely on prostate biopsy. About 20 % of these patients treated for a LG or IG PrCa might have harboured HG PrCa that remained undetected [34]. Third, the mpMRI techniques used in our study (T2-WI, DWI and MRSI, without DCE) are a reflection of the technical evolution during the inclusion period (2002−2014) and differ slightly from the mpMRI protocol that we currently use.…”
Section: Discussionmentioning
confidence: 99%
“…In our study group 332 patients (40.0 %) treated with radiation therapy were included although the diagnosis in these patients relies solely on prostate biopsy. About 20 % of these patients treated for a LG or IG PrCa might have harboured HG PrCa that remained undetected [34]. Third, the mpMRI techniques used in our study (T2-WI, DWI and MRSI, without DCE) are a reflection of the technical evolution during the inclusion period (2002−2014) and differ slightly from the mpMRI protocol that we currently use.…”
Section: Discussionmentioning
confidence: 99%
“…Although the TRUS-guided prostate needle biopsy remains the gold standard for diagnosis of prostate cancer, the accuracy of the biopsy is limited. According to Rabbani et al, in the case of a sextant biopsy, 23% of all tumors are not diagnosed [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, most recent studies have suggested that biopsy of alternative areas of the prostate, such as the TZ and the ALH, may increase the rate of prostate cancer detection. [4][5][6]8,14 For example, Eskew et al 14 15 reported, in their prospective study, that the cancer detection rates with 6-core and 12-core biopsy regimens were almost identical (26% and 27%). Moreover, to our knowledge, there seem to be few studies evaluating the significance of sampling in addition to the standard sextant biopsy in a large series of Japanese men.…”
Section: Discussionmentioning
confidence: 99%
“…10,17 However, of the 101 patients diagnosed as having prostate cancer, 11 had a positive core only in the ALH; that is, the increase in the cancer detection rate yielded by obtaining two extra cores from the ALHs was 10.9%, showing less impact of additional sampling on the cancer detection rate than that described in recently reported studies. [4][5][6]8,14 Possible explanations for this discrepancy are as follows. (1) Two additional cores may not be enough to affect the cancer detection rate, due to the small size of the tumors currently detected in the PSA screening era.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation